1993
DOI: 10.1095/biolreprod48.4.874
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Endometrial Oxytocin Receptors, Oxytocin-Stimulated Phosphoinositide Hydrolysis and Prostaglandin F2α Secretion in Vitro, and Plasma Concentrations of Ovarian Steroids before and during Corpus Luteum Regression in Cyclic Heifers1

Abstract: Oxytocin stimulates secretion of endometrial prostaglandin (PG) F2 alpha and induces endometrial phosphoinositide hydrolysis around the time of regression of the corpus luteum (CL) in cows. This study investigated the relationship between endometrial oxytocin receptors, oxytocin-stimulated phosphoinositide hydrolysis and PGF 2 alpha secretion in vitro, and plasma concentrations of ovarian steroids before and during CL regression in cyclic heifers (i.e., Days 13-19 post-estrus). Reproductive tracts were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 41 publications
5
27
1
2
Order By: Relevance
“…This OT concentration was comparable to the affinity of the bovine endometrial OT receptor reported previously [7,11]. Consequently, our present results indicate that PGF 2α secretion induced by OT in the endometrium occurred through ligand binding to the OT receptor.…”
Section: Discussionsupporting
confidence: 90%
“…This OT concentration was comparable to the affinity of the bovine endometrial OT receptor reported previously [7,11]. Consequently, our present results indicate that PGF 2α secretion induced by OT in the endometrium occurred through ligand binding to the OT receptor.…”
Section: Discussionsupporting
confidence: 90%
“…The oxytocin-binding assay was performed as described previously [20,21], with slight procedural modifications. The [ 3 H]-oxytocin (OT) was diluted in oxytocin diluting buffer #3 (25 mM Tris-HCl, 0.01% NaN 3 , 0.2% bovine serum albumin, 20 mM manganese chloride, pH 7.4) to a concentration of 2 pmol/50 mL (approximately 163,000 disintegrations/min/50 mL), from which serial dilutions between 0.125 and 2.0 pmol [ 3 H]-OT/50 mL were made.…”
Section: Tissue Processing and Oxytocin-binding Assaymentioning
confidence: 99%
“…Endometrial tissue was evaluated for OTR binding by use of a modified procedure of Hazzard and Stormshak [14] adapted from original methods of Mirando et al [16]. Specific binding of OT to its receptor was determined with [ 3 H] OT (range of concentrations 0.625-10 nM; 44.5 Ci/ mmol, New England Nuclear, Boston, MA) and labeled ligand plus a 200-fold excess of unlabeled OT to correct for nonspecific binding.…”
Section: Otr Assaymentioning
confidence: 99%